Flipped Classroom Dalam Pembelajaran Life Skill Siswa Berkebutuhan Khusus - Widajati, Wiwik; Purbaningrum, Endang; Mahmudah, Siti; Anggraeny, Diah (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2022)
The flipped classroom learning strategy provides opportunities and support for students with special needs to construct knowledge, complete assignments, and learn life skills learning materials in a comfortable, independent atmosphere according to their potential and needs and through various media, including videos, books, and the internet. The purpose of this study was to examine the effect of the flipped classroom on improving the life skills of students with special needs. This research design is one group pre-test-post-test design. The research subjects were students with special needs at the Extraordinary High School in Surabaya. Data collection using performance tests. Data analysis used the Wilcoxon marked level test (match pairs test). The results showed that the life skills of students with special needs after implementing the flipped classroom were better than before learning with the flipped classroom. Based on the results of the analysis of research data with a significance level of 0.05, the results obtained Zh = 2.52 is greater than the Z table value of 1.96 (Zh > Zt). This means that there is an effect of the flipped classroom on the learning outcomes and life skills of special needs students.